Critical Analysis of the Implementation of Academic Ability Tests (TKA) in Vocational Secondary Schools: A Descriptive-Analytical Literature Review of the Impact of Permendikdasmen No. 9 of 2025 - Hertanto, Yudhi; Miranti, Ira (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
Ministry of Primary and Secondary Education Regulation No. 9 of 2025 introduces the Academic Ability Test (TKA) as a standard evaluation instrument. Its implementation in Vocational High Schools (SMK), which focus on practical competencies and work readiness, raises the potential for conflict. This study aims to analyse the potential impact and challenges of implementing the TKA in SMKs and its implications for vocational pedagogy. The research method used a descriptive-analytical qualitative approach with a literature review. A policy implementation diagnostic framework and a conflict-ambiguity typology model were used to assess the compatibility between the TKA and the objectives of vocational education. The results of the analysis shed light that there is a dissonance between the academic focus of TKA and the competency-based philosophy of SMK. Implementation challenges are predicted to be systemic, including obstacles related to policy standards, resource availability, and implementer disposition. In addition, at the school level, covert resistance and strategic adaptation to protect the identity of vocational pedagogy are likely to emerge. This policy is categorised as ‘Political Implementation,’ where formal compliance may occur, but actual practice in the field adapts to the needs and characteristics of vocational schools. It can therefore be concluded that the application of standard academic evaluation in vocational schools risks weakening vocational pedagogy and may compromise the core mission of vocational education.